2015
DOI: 10.1111/jfr3.12184
|View full text |Cite
|
Sign up to set email alerts
|

Case study results from southeast Houston, Texas: identifying the impacts of residential location on flood risk and loss

Abstract: Despite the increasing economic losses from floods in coastal communities, little observational research has been done at a fine spatial scale to identify the relative influence of residential location in predicting adverse economic impacts. In response, this study conducts a parcel‐level analysis of flood losses to identify the influence of specific location‐based variables on property damage from multiple flood events. We statistically isolate the effect of multiple location‐based characteristics on insured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 42 publications
(46 reference statements)
1
22
0
Order By: Relevance
“…Of the 37 casualties in Harris County, only 22 % occurred within the designated 100-year floodplain -used as the primary delineation of flood risk in the United States -and 49 % within the 500-year floodplain. This is in line with previous research which finds that in the greater Houston region, the 100-year floodplains have served as a poor predictor of the location of damaging flooding (Highfield et al, 2013;Brody et al, 2018;Blessing et al, 2017). While the flooding from Hurricane Harvey should be expected beyond the 100-year and even 500-year floodplains, our finding also suggests that high-hazard areas outside of the floodplain, such as low water crossings, have not been adequately delineated or communicated to the public.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Of the 37 casualties in Harris County, only 22 % occurred within the designated 100-year floodplain -used as the primary delineation of flood risk in the United States -and 49 % within the 500-year floodplain. This is in line with previous research which finds that in the greater Houston region, the 100-year floodplains have served as a poor predictor of the location of damaging flooding (Highfield et al, 2013;Brody et al, 2018;Blessing et al, 2017). While the flooding from Hurricane Harvey should be expected beyond the 100-year and even 500-year floodplains, our finding also suggests that high-hazard areas outside of the floodplain, such as low water crossings, have not been adequately delineated or communicated to the public.…”
Section: Discussionsupporting
confidence: 90%
“…During future events, preventive closure of these areas could be considered. Loss of life is influenced by individuals' behavior and the warning and evacuation strategy by the government (Chowdhury et al, 1993;French et al, 1983;Parker et al, 2009). The events during Harvey can also be utilized to evaluate and improve the performance of the evacuation strategy and emergency management for the region, also addressing the need for timely evacuation from specific highrisk areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than a half of the simulated inundation extent (55%) was found outside of the FEMA flood maps, while 70% of FEMA flood maps (637 km 2 out of 915 km 2 ) was identified to be inundated during the Hurricane Harvey flooding. Given that the FEMA flood maps are not based on the precipitation from Hurricane Harvey and that they are generally considered a poor predictor of the location of damaging flooding in previous studies [4,44,45], some differences may be justifiable. The widespread discrepancies outside of the flood zones, however, do raise questions as to whether the conventional flood mapping approaches, which focus on fluvial flooding [46], are appropriate, particularly for urban areas where large risks exist also from pluvial flooding, as shown in this work.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that the flooding during Hurricane Harvey is expected to have a much higher return period in the greater Houston region, thus flooding can be expected beyond the 100-year and even 500-year flood zone. However, previous research has also shown that in the greater Houston region, the 100-year floodplains are a poor predictor of the location of damaging flooding during past events (Highfield, Norman, and Brody, 2013;5 Blessing, Sebastian, and Brody, 2017) and that NFIP claims can occur far outside of the delineated flood hazard zones (Brody et al 2015). As future work it is recommended to recreate and map the flood conditions during Harvey based on modelling and field observations to better understand the flood conditions at the time and location of fatalities.…”
Section: Discussionmentioning
confidence: 99%